A framework of critical success factors of cloud based project management software adoption - L. I. Assalaarachchi; M. P. P. Liyanage; C. Hewagamage (International Journal of Information Systems and Project Management)
Project Management (PM) software is an enabler of project success and is now being offered as a cloud-based software with the advancement of cloud computing. This research was conducted to explore the critical success factors affecting the adoption of cloud-based PM software. Semi-structured interviews were carried out with Information Technology (IT) professionals following the qualitative approach. Through thematic analysis, four themes were identified as areas considered when adopting cloud-based PM software: technological, organizational, environmental, and vendor-specific factors. Relative advantage, ease of use, compatibility, and reliability were categorized as the technological factors. Organization size, the technological readiness of the organization, employee willingness, top management support, and change management process were identified under organizational factors. Competitors' adoption, industry trends, and dedicated internet connectivity were identified under environmental factors. Additionally, features such as maintenance and service support from the vendor, popularity of the brand name, and availability of free trials emerged as vendor-specific factors.